Digital transformation and agricultural transportation synergy resilience: path and spatial effects - Zhang, GenLin; Chai, JunJie; Xie, Jie (Frontiers in Sustainable Food Systems, 2025)
PurposeThe purpose of this study is to explore the relationship between the transportation industry and agricultural resilience, focusing on how the digital economy promotes synergistic resilience so as to promote the improvement of agricultural industry resilience. The research goal is to provide policy recommendations for regional agricultural development, with particular attention to how to make more effective use of industry synergies to enhance agricultural resilience in the context of digital transformation.Design/methodology/approachBased on the panel data of 31 provinces from 2012 to 2022, this study first uses the coupling coordination model to analyze the relationship between industries. Then, the benchmark regression and mediating effect model are used to study how the digital economy promotes the coordinated development of the industry. Finally, the spatial Durbin model is used to test the spatial differences in the synergy between the two industries.FindingsThe results reveal prevalent “high coupling but low coordination” between agricultural and transportation resilience, with coupling degrees mostly above 0.85 yet coordination degrees below 0.4. Digital transformation significantly enhances industry synergy resilience (β = 0.569, p < 0.01), with regional resource allocation mediating nearly half of this effect. Spatial analysis further confirms notable positive spillover effects (β = 0.483, p < 0.01), especially in eastern coastal provinces.Originality/valueThis paper proposes a synergistic effect analysis framework combining digitization and regional differences, which provides a new perspective and method for academic research in related fields. The research results provide policymakers with regional differentiation results and different reference suggestions based on regional characteristics.